Siam weed based hydrogel hybrid for tissue engineering - Mohamed, Nor Shamsiah (2020)
Tissue engineered skin grafts have been considered as an auxiliary for replacement of damaged skin due to burns and injury. In previous studies, gelatin hybrid with natural remedy were used in order to create 3D environment for the skin grafts. However, these gelatin hybrids were not sufficient to promote the healing process especially for infected wounds due to lack of therapeutic properties and their mechanical properties are yet to be defined. In this research, Siam Weed therapeutic properties promote healing process and its mechanical properties were enhanced by gelatin and electrospinning technique to produce Siam weed-gelatin electrospun scaffold as a successful 3D skin tissue engineering grafts. The effects of content of Siam weed extracts on the electrospun scaffolds are determined using scanning electron microscopy, Fourier Transfom Infrared spectroscopy and degradation study of solution properties. The results indicated that concentration affects the solution properties such as viscosity, conductivity and ultimately the fiber diameter. The fibrous meshes were then crosslinked with glutaraldehyde vapor and its mechanical properties were determined by tensile . The value of tensile strength of the crosslinked fibrous scaffold was higher than that of human skin proving that it has high potential to be a successful skin graft when immobilized at the wound site. Cell proliferation study of the Siam weed extracts indicated that the extracts had significantly stimulate cell proliferation with a strong response at the concentration of 25 µg/ml therefore giving the optimum proliferation of the cells. The results implied the possibility of using Siam weed-gelatin fibrous scaffold as a promising candidate for tissue engineered skin grafts